Phosphine‐Functionalized Syndiotactic Polystyrenes: Synthesis and Application to Immobilization of Transition Metal Nanoparticle Catalysts. Issue 62 (1st September 2022) - Jiang, Lei; Wang, Yinran; Sun, Hanyang; Fu, Tingting; Hou, Zhaomin; Guo, Fang
Abstract: The precise control of monomer sequence and stereochemistry in copolymerization is of much interest and importance for the synthesis of high performance materials, but studies toward this goal have met with only limited success to date. The coordination polymerization of diphenylphosphinostyrene ( p ‐StPPh2 and o ‐StPPh2 ) and its copolymerization with styrene (St) by (C5 Me4 SiMe3 )Sc(CH2 C6 H4 NMe2 ‐ o )2 have been achieved for the first time to afford a new series of phosphine functionalized syndiotactic polystyrene. By the design of the polymer structure, the copolymer of o ‐StPPh2 and St (poly( o ‐StPPh2 ‐ alt ‐St)‐ b ‐ s PS) containing o ‐StPPh2 and St atactic alternating copolymer block and syndiotactic polystyrene block ( s PS) showed excellent thermal stability and chemical resistance. The simple combination of the triphenylphosphine and syndiotactic polystyrene realized the stable immobilization of metal nanoparticles to afford highly robust metal@poly( o ‐StPPh2 ‐ alt ‐St)‐ b ‐ s PS nanocatalysts at high temperature and various atmospheres. The Cu@poly( o ‐StPPh2 ‐ alt ‐St)‐ b ‐ s PS catalyst can serve as a highly efficient heterogeneous catalyst for the synthesis of quinoline derivatives by acceptorless dehydrogenative coupling of o ‐aminobenzylalcohol with ketones. Abstract : A novel phosphine‐functionalized syndiotactic polystyrenes composed of o ‐diphenylphosphinostyrene and styrene alternating copolymer block and syndiotactic polystyrene block prepared by the copolymerization of o ‐diphenylphosphinostyrene with styrene using (C5 Me4 SiMe3 )Sc(CH2 C6 H4 NMe2 ‐ o )2 showed not only thermal stability and chemical (solvent) resistance, but also excellent performance of immobilization of transition metal nanoparticle catalysts.